1998
DOI: 10.1111/j.1348-0421.1998.tb02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Prevotella intermedia and Prevotella nigrescens in Periodontal Health and Disease

Abstract: The incidence of black‐pigmented rods (BPRs), especially Prevotella intermedia and Prevotella nigrescens, in periodontal health and disease were examined. Furthermore, the degradative enzyme activities of P. intermedia were compared among the strains from periodontal health and disease. Microbiological specimens were collected from subgingival crevice or periodontal pocket by paper point. The BPRs were found in 71.1% of periodontally healthy subjects (n = 45), and in 47.1% of healthy sites (n = 34) and 87.8% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 29 publications
1
30
0
3
Order By: Relevance
“…Several studies have reported the increased incidence of P. intermedia in periodontal lesions, while P. nigrescens seems to be associated with endodontic infection, adult gingivitis and healthy gingival sites [6^10]. We have also observed that P. intermedia is predominant in periodontal disease, whereas P. nigrescens was predominant in periodontally healthy subjects [11]. However, some studies have reported contradictory results regarding the occurrence of Prevotella in the oral cavity [12,13].…”
Section: Introductionsupporting
confidence: 54%
“…Several studies have reported the increased incidence of P. intermedia in periodontal lesions, while P. nigrescens seems to be associated with endodontic infection, adult gingivitis and healthy gingival sites [6^10]. We have also observed that P. intermedia is predominant in periodontal disease, whereas P. nigrescens was predominant in periodontally healthy subjects [11]. However, some studies have reported contradictory results regarding the occurrence of Prevotella in the oral cavity [12,13].…”
Section: Introductionsupporting
confidence: 54%
“…Faecalibacterium are commensal human gut bacteria with apparent anti-inflammatory activity (Sokol et al, 2008(Sokol et al, , 2009, which may ultimately be investigated with a view to its use as a probiotic to treat Crohn's disease, colitis, and irritable bowel syndrome (Kirjavainen et al 2001). Prevotella are commensal microbes in rumen and hind gut of cows and sheep and in humans, where they help the breakdown of proteins and carbohydrates (Yildirim et al, 2010); it is also associated with periodontal disease in humans (Maeda et al, 1998). Although Catenibacterium are also associated with the human gut, little is known about this genus (Kageyama and Benno, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This is a precursor to progression to periodontitis. This is buttressed by the fact that P. intermedia has been known to increase the activity of degradative enzymes under certain conditions, and supports the progression to periodontitis [12].…”
Section: Discussionmentioning
confidence: 99%